Pengembangan Strategi Pemasaran Produk UMKM Perempuan Melalui E-commerce Di Kelurahan Rembang Kota Blitar - Zanetta Najlaa Putri Arfi; Dewi Deniaty Sholihah (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
The presence of the Corona Virus Pandemic has greatly affected the community in various sectors. One of the most visible impacts is on the MSME (Micro, Small and Medium Enterprises) economic sector. MSME business actors have experienced many difficulties in selling and exhibiting their products so that their income levels have decreased. MSME players also cannot remain silent, they must continue to sustain their business by utilizing advances in information technology which currently has a significant impact on society in supporting various business activities, both large and limited in scope, so that businesses can be recognized globally. Therefore, it is important to have media that can be easily reached by potential buyers, but MSME business actors in Rembang City are still lacking and not fully familiar with digital marketing. Thus, assistance is provided to MSME players regarding the use of digital marketing so that it can make it easier for MSME players to market their products through social media and e-commerce. Community service is carried out by providing socialization and training to MSME business actors on how to create, promote, and sell products through e-commerce businesses such as shopee. With the community empowerment through socialization and training for MSME players in Rembang Village, Blitar City, it is hoped that it can bring changes in a better direction so that they can continue their business fields.